2023
DOI: 10.3390/nu15061520
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a School-Based Culinary Programme on 9- and 10-Year-Old Children’s Food Literacy and Vegetable, Fruit, and Breakfast Consumption

Abstract: School-based culinary courses may increase children’s food literacy and improve their eating behaviours. This study assessed the impact of a school-based culinary programme on 9- and 10-year-old students’ food literacy and vegetable, fruit, and breakfast consumption. This cluster quasi-experimental trial compared 88 grade 4 and 5 students who participated in the Apprenti en Action programme to 82 students who did not. Students’ food literacy and eating behaviours were assessed with a self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…These findings underscore the importance of enhancing food and nutrition literacy among children, and public health interventions should focus on improving food and nutrition-related knowledge and skills to enhance child's fruit consumption. Nevertheless, studies have shown that nutrition education can improve food and nutrition literacy but has no significant impact on fruit and other foods consumption (16,41). In reality, food consumption is influenced by individual and environmental factors, which can be better understood through a socio-ecological model (42).…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the importance of enhancing food and nutrition literacy among children, and public health interventions should focus on improving food and nutrition-related knowledge and skills to enhance child's fruit consumption. Nevertheless, studies have shown that nutrition education can improve food and nutrition literacy but has no significant impact on fruit and other foods consumption (16,41). In reality, food consumption is influenced by individual and environmental factors, which can be better understood through a socio-ecological model (42).…”
Section: Discussionmentioning
confidence: 99%